Love in a cold war - Christenson, Anna (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2015)
A collection of short stories in two parts written in realist and fabulist styles. The first part looks at the post-war generation of baby boomers growing up in the American Midwest. The second half follows an American abroad and explores themes of disintegration, the shifting power balance in relationships and the terrible hole at the core of expatriate identity.
Keywords: South African fiction (English) -- 21st century